Effectiveness of Using Mnemonic Methods to Improve Student Learning Outcomes in Social Sciences Subjects - Andini Silviana Putri; Desy Safitri; Sujarwo (AIQU: Journal Multidiscipliner of Science, 2024)
and Final Semester Summative Assessment (ASAS) in the Social Sciences subject class VII A Odd Semester 2023/2024 Academic Year at SMP Negeri 163 Jakarta, it shows that the average test score is still low or does not meet the Minimum Completeness Criteria (KKM), namely 77. This research was conducted in class VII-A of SMP Negeri 163 Jakarta for two months from March to April 2024. The aim of the research was to improve the learning outcomes and activity of class VII A students at SMP Negeri 163 Jakarta. The research method used is classroom action research, with data collection techniques through written tests, observation and documentation. The results of this research show that: 1) Using the Mnemonic Method in Social Sciences subjects can improve student learning outcomes. It is known that in cycle 1, the percentage of student learning outcomes was 31% with an average learning outcome of 71.25. In cycle 2 it increased to 53% with an average learning outcome of 76.94 and in cycle 3 there was an increase to 78% with an average learning outcome of 83.33. 2) The use of the Mnemonic Method also increases student activity in the aspects of asking, answering and assignments.